Factors Influencing the Firm Performance of Small and Medium Enterprises: A Case Study of Mogadishu, Somalia (Journal of Social Sciences Review, 2025)
Small and Medium Enterprises (SMEs) play a major role in the country’s economies, particularly in developing countries where SMEs contribute particularly to the employment era and are an essential channel to poverty decline. This study investigates the influential factors (Social, Cultural, Innovation, Human Resources, Local Government) affecting the Firm Performance of Small and Medium Enterprises in Mogadishu, Somalia. Data for the current study has been gathered through a structured questionnaire from 218 SMEs in Mogadishu, Somalia. Diagnostic tests, confirm the reliability and validity of the data used in the current study. The findings of the study showed that all factors (Social, Cultural, Innovation, Human Resources, Local Government) positively and particularly influence the financial performance of Small and Medium Enterprises (SMEs) in Mogadishu, Somalia. The study suggests that policymakers and businesses consider key contributing factors for the performance of SMEs, especially in Somalia.
Keywords: SMEs; Cultural Factor; Innovation; Human Resource; Local Governance; Firm Performance; Economic Development